Mitochondrial Subtype Identification and Characterization. Issue 1 (26th June 2018) - Daniele, Joseph R.; Heydari, Kartoosh; Dillin, Andrew
Abstract: Healthy, functional mitochondria are central to many cellular and physiological phenomena, including aging, metabolism, and stress resistance. A key feature of healthy mitochondria is a high membrane potential (Δψ) or charge differential (i.e., proton gradient) between the matrix and inner mitochondrial membrane. Mitochondrial Δψ has been extensively characterized via flow cytometry of intact cells, which measures the average membrane potential within a cell. However, the characteristics of individual mitochondria differ dramatically even within a single cell, and thus interrogation of mitochondrial features at the organelle level is necessary to better understand and accurately measure heterogeneity. Here we describe a new flow cytometric methodology that enables the quantification and classification of mitochondrial subtypes (via their Δψ, size, and substructure) using the small animal model C. elegans . Future application of this methodology should allow research to discern the bioenergetic and mitochondrial component in a number of human disease and aging models, including, C. elegans, cultured cells, small animal models, and human biopsy samples. © 2018 by John Wiley & Sons, Inc.